THE EFFECT OF CONVENIENCE ON INTEREST IN REUSING THE LINKAJA APPLICATION THROUGH TRUST - Mutia Arda; Dewi Andriany (RADJA PUBLIKA, 2024)
Money is not only in physical form (cash), but there is already technology that makes money into an intangible object (non-cash) such as electronic money or what is commonly called e-money, one of which is LinkAja, a digital financial service from Telkomsel and a member of the State-Owned Enterprises. The number of LinkAja users is still smaller than OVO, Gopay, ShopeePay, and DANA which merged with other e-commerce companies. This study aims to determine the effect of convenience on the interest in reusing the LinkAja application through trust, both directly and indirectly. This study uses a quantitative approach with path analysis techniques using the partial least square–structural equation model (PLS-SEM) technique. The results of the study showed that there was an effect of convenience on trust in using LinkAja for students, an effect of trust on interest in using LinkAja for students and an effect of convenience on interest in reusing through trust as a moderating variable in the use of LinkAja for students. However, the results of the study showed no effect of convenience on interest in using LinkAja for students. And the results of the R-Square Adjust value test obtained the results that the path model using the moderating variable is 0.537 and 0.505. In other words, the ability of variable X, namely Ease in explaining variable Z, namely Trust, is 53.7%, thus the model is classified as moderately substantial and the ability of variable X, namely ease in explaining variable Y, namely Reuse Intention, is 50.5%, thus the model is classified as substantial (moderate).